ANALISIS SERVICE QUALITY PADA TRANSPORTASI DARING BERDASARKAN PERSPEKTIF PENGGUNA - Abu Nubli Fauzan Addani (2020)
There are still many services that are not optimal, such as lack of updates for some features and frequent system errors that make less than the maximum service provided. This research is intended to see the service quality of all types of services available in online transportation services that exist today. This research uses quantitative methods, the process of collecting data using questionnaires using several service quality indicators. Data processing uses the Partial Least Square SEM (PLS SEM) approach with SmartPLS 3.2.8 software. Some indicators used include reputation from the user's side, transaction security perceived by the user, and the reliability of the existing system. As the results of this analysis it will be concluded to be a picture for the users of existing service quality and also input for online transportation service providers.